2011
DOI: 10.1002/jcb.23142
|View full text |Cite
|
Sign up to set email alerts
|

ER‐resident Gi2 protein controls sar1 translocation onto the ER during budding of transport vesicles

Abstract: In our previous study, fluoride ([AlF(4) ](-) ) disturbed ER-to-Golgi transport through the activation of ER-resident heterotrimeric G protein (ER-G protein). Therefore, ER-G protein may be implicated in ER-to-Golgi transport at the early stage prior to coat protein assembly. Sar1 translocation onto the endoplasmic reticulum (ER) membrane is suppressed by non-selective protein kinase inhibitor H89, suggesting the participation of H89-sensitive kinase in this process. To investigate the involvement of ER-G prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, the involvement of Gβγ in UPR in mammalian cells has yet to be demonstrated. Lastly, a recent report linked Gα i2 to the small GTPase Sar1, a protein that regulates the generation of COPII vesicles from the ER membrane which are destined to the Golgi [95]. It was shown that the Gi protein activator, mastoparan 7, suppressed the translocation of Sar1 to the ER in a cell free, microsomal system, while a negative regulator of the Gi protein, pertussis toxin, recovered this suppression.…”
Section: G Proteins At Organellesmentioning
confidence: 99%
“…However, the involvement of Gβγ in UPR in mammalian cells has yet to be demonstrated. Lastly, a recent report linked Gα i2 to the small GTPase Sar1, a protein that regulates the generation of COPII vesicles from the ER membrane which are destined to the Golgi [95]. It was shown that the Gi protein activator, mastoparan 7, suppressed the translocation of Sar1 to the ER in a cell free, microsomal system, while a negative regulator of the Gi protein, pertussis toxin, recovered this suppression.…”
Section: G Proteins At Organellesmentioning
confidence: 99%